Survey on user’s mobility behavior modelling in urban environment - Fengli XU; Yong LI (Tongxin xuebao)
Urban environment has become a typical scenario for areas of mobile communication,transportation scheduling,disease controlling and so on,and modelling user’s mobility behavior plays an important role in these key applications.The research development in this area was combed and summarized,which provided a literature review for related works.Firstly,the main challenges in urban mobility modelling were discussed as well as the corresponding key scientific problems,which included mobility data augmentation,urban structure-aware mobility behavior discovering,multi-scale mobility behavior prediction and mobility data privacy protection.Furthermore,according to these key scientific problems,the recent developments and up-to-date scientific output in this area were summarized,which paved the way for future research.